EVALUATION OF THE EFFECTS OF ZINC APPLICATION METHODS ON TRITICUM AESTIVUM L. YIELD AND GRAIN QUALITY UNDER CHROMIUM STRESS - Rimsha Ishtiaq, Muhammad Waqas, Memoona Aziz, Hafsa Farooq, Javeria Muhammad Ahmad, Mehreen Hassan, Khazeema Khan, Muhammad Hafeez Ul Haq, Muhammad Taqqi Abbas (Chelonian Research Foundation, 2024)
Zinc (Zn) malnutrition is widespread in developing countries where cereal grains are used as staple food. Zn efficient wheat genotypes have been developed to minimize Zn malnutrition; however, there is another threat of accumulation of heavy metals in grains from heavy metal contaminated soils which would contaminate the food chain. Present study was conducted to check the impact of different Zn application methods on growth, yield and accumulation of Zn and chromium (Cr) in grains of a Zn efficient wheat cultivar grown under Cr contamination. The experiment was comprised of two factors including three contamination levels of Cr (0 ppm, 5 ppm, 15 ppm) and three Zn application methods (seed coating, soil application and foliar spray). Akbar-19 was used in this experiment which is a recent Zn efficient wheat cultivar developed for improving Zn concentration in grains of wheat. Observations including plant height, shoot length, shoot fresh weight and dry weight, spike length, 100 grains weight, photosynthetic efficiency, relative water content were recorded. Results showed that due to Cr stress, growth parameters, biological yield, photosynthetic yield and yield of wheat cultivar reduced at higher Cr level, i.e, 15 ppm. It was observed that application of Zn through seed coating, soil application and foliar spray significantly ameliorates the toxicity of Cr. Overall seed coating, foliar spray and soil application of Zn improved all parameters but grain Zn content was significantly increased through foliar spray. Soil application was also effective and play mitigative role in the presence of Cr toxicity.